THE EFFECTS OF USING COOPERATIVE SCRIPT METHOD TO THE SPEAKING ABILITY OF THE FIRST YEAR STUDENTS OF SMK TELKOM PEKANBARU - Rossalia Amanda Rossalia Amanda; Eliwarti Eliwarti '; Desri Maria Desri Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This experimental research aimed to find out the effect of using Cooperative script method to speaking ability of first year students of SMK Telkom Pekanbaru. Most of the students of SMK Telkom Pekanbaru often face some problems in speak English such as: lack of vocabulary, afraid of making mistake, not brave enough to speak in English and less participate in classroom. To overcome the problem, the writer used Cooperative Script Method in teaching and learning process. The population was the first year students of SMK Telkom Pekanbaru, while the sample was X Telkom as experimental class and X TKJ 1 as control class. The writer used cluster sampling technique to decide the sample and the instrument of this research was test in the form of dialogue test. The test included some topics such as; expressions of capability and incapability, asking and giving direction and invitation. The students’ scores were graded by the three raters using Brown’s scale and analyzed using t-test formula. The writer used the level of significance at 0.05 (5%). After being calculated, the value of t-observe) was 3.42, whereas the value of t table on the df (degree of freedom) 20 was 2.086. Therefore, the alternative hypothesis that there is a significant difference in speaking achievement between the students who are taught before the use of cooperative script method and after the use of cooperative script method was accepted and its null hypothesis was rejected. In conclusion, using Cooperative Script method advance speaking ability of the first year students of SMK Telkom Pekanbaru significantly.Keywords: Cooperative Script Method, Speaking Ability